Quality Factors in Documentary Translation - Pinto, María (Meta, 2001)
AbstractWell aware of the difficulties involved in integrating translating models and quality systems, we offer an overview of relevant developments in the field. Particular emphasis is placed on the pragmatic connotations of translation and on the methodological aspects of the Quality Paradigm, an approach to documentary translation that focuses activity on the target user.